Effects of Sensation Seeking, Creator Attractiveness, Content Novelty, and Credibility on Branded Entertainment - Kim, Jungryum; Hong, Dahyun; Jun, Jong Woo (Indian Journal of Marketing, 2025)
Purpose : This study explored the effects of branded entertainment on the information processing of consumers. It proposed modeling factors influencing consumer behaviors. Methodology : Using Korean female consumers as research samples, this study collected survey samples, and tried to identify the roles of consumer psychological factors, creator attractiveness, and content factors on purchase intention and word-of-mouth intention. Findings : The findings of this study showed that sensation-seeking influenced both purchase intention and word-of-mouth intention. Creator attractiveness was related in positive ways, and content novelty and content credibility influenced purchase intention and word-of-mouth intention. Lastly, attitudes toward content was connected to both purchase intention and word-of-mouth intention. Practical Implications : The hierarchical regression model of this study suggested certain academic implications and could also provide managerial implications in terms of the production of branded entertainment, especially focusing on creators’ attractiveness and content styles. The research product was limited to only cosmetics, and future research will be necessary with more diverse products. Originality : Unlike prior research on influencer marketing, the current work built an attractiveness model of influencers incorporating sensation seeking, novelty, and ad credibility.